Formulation and Antifungal Activity of Piper betle L. Leaf Extract in Emulsion Gels Against Candida albicans - Widyasari Putranti; Chairisty Asterina; Hardi Astuti Witasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Candidiasis is the most common fungal infection in humans and is a form of primary and secondary infections of C. albicans. Betel (Piper betle L.) leaf extract has been reported to exhibit efficacious antifungal effects against C. albicans. Emulsion gels, a type of topical dosage form, can deliver hydrophilic and hydrophobic drugs and perform multiple and controlled releases. This research aimed to determine the antifungal activity and physical properties of emulsion gels formulated from betel leaf extract. The dried betel leaves were extracted by maceration with alcohol 95%. Then, with different concentrations (1, 2, and 4%), the extract was formulated into emulsion gels. These dosage forms were later subjected to antifungal activity testing against C. albicans using the cup plate diffusion method that involved Mycoral Cream® for comparison. In this test, the intensity of the activity was determined by measuring the diameter of the formed inhibition zone. The second test evaluated the physical characteristics of the dosage forms, including organoleptic properties, pH, adhesion, dispersion, and viscosity. These data were analyzed using the Mann-Whitney method, and the conclusion was withdrawn from describing the results quantitatively. The reaction yield of the extraction was 9.702%. The analysis results showed that emulsion gels containing 1, 2, and 4% of betel leaf extract created zones of inhibition with diameters of 5.3 ± 0.29, 6.2 ± 0.29, and 10.2 ± 0.41 mm, respectively. As for the physical properties, they differed in pH (6.39 ± 0.120, 6.17 ± 0.132, 5.66 ± 0.123), spreadability (1.849 ± 0.45, 1.816 ± 0.051, 1.771 ± 0.092 g.cm.s-1), adhesion (110 ± 10.8, 126.3 ± 8.5, 142.7 ± 13.50 seconds), and viscosity (2640.35, 1992.95, 2162.12 cps), respectively. The betel leaf emulsion gels exhibited antifungal activity against C. albicans (p <0.05) and met the physical requirements of semi-solid dosage forms.